Bovine heat stress management: current amelioration approaches and the case for a novel mitogenomic strategy - Scerri, Tiarna Macey; Lomax, Sabrina; Clark, Cameron Edward Fisher (Frontiers in Animal Science, 2023)
An expansive body of literature is dedicated towards addressing the multi-faceted issue of bovine heat stress. This review firstly evaluated existing knowledge about the acute bovine heat stress response. Despite these papers being comprehensive, minor research gaps and biases somewhat limit their applicability. Categorising current management strategies under either a 'reactive' or 'preventative' approach, the review also evaluated the utility of strategies within each approach. Strategies that achieve individualised symptom detection and treatment were found to be the most practically effective reactive strategies. Genotypes that functionally increase the stability of proteins involved in the heat stress response and therefore increase an animal's capacity for heat tolerance were identified as being among the most promising preventative strategies. Both approaches are generally limited by significant implementation costs for farmers and a lack of literature comparison between strategies for the best management outcome. A strong case is provided for further investigation into the role of mitochondrial genotypes for improved cattle heat tolerance. Overall, the review provides a balanced assessment of progress within heat stress scholarship and tenders a novel perspective that will inform further original work.